2017
DOI: 10.1007/s10103-017-2416-2
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of S100A8 in skin rejuvenation with the 1064-nm Q-switched Nd:YAG laser

Abstract: The 1064-nm Q-switched Nd:YAG laser is demonstrated to be effective for non-ablative skin rejuvenation, but the molecular mechanism by which dermis responses to laser-induced damage and initiates skin remodeling is still unclear. HaCaT cells and 3T3 skin fibroblasts were irradiated with the 1064-nm Q-switched Nd:YAG laser at the different doses. Then, cells were collected and lysed for PCR and Western blot analysis. Cell viability was detected by Cell Counting Kit-8 (CCK-8) before and after laser irradiation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Q-switched 1064-nm Nd: YAG laser (1064-QSNYL) was the first laser used for nonexfoliative skin rejuvenation. 4 The effect of nonexfoliative laser on skin rejuvenation is mainly to damage skin dermis through the photothermal and mechanical effects, so that part of the collagen is denatured, thereby activating the benign self-repair process of the tissue and stimulating fibrogenesis cell proliferation, while promoting the reorganization and proliferation of collagen. 5,6 As early as 1997, studies have shown that 1064-QSNYL can improve skin texture, elasticity, and facial wrinkles.…”
Section: Introductionmentioning
confidence: 99%
“…Q-switched 1064-nm Nd: YAG laser (1064-QSNYL) was the first laser used for nonexfoliative skin rejuvenation. 4 The effect of nonexfoliative laser on skin rejuvenation is mainly to damage skin dermis through the photothermal and mechanical effects, so that part of the collagen is denatured, thereby activating the benign self-repair process of the tissue and stimulating fibrogenesis cell proliferation, while promoting the reorganization and proliferation of collagen. 5,6 As early as 1997, studies have shown that 1064-QSNYL can improve skin texture, elasticity, and facial wrinkles.…”
Section: Introductionmentioning
confidence: 99%